AB0083 Anti-inflammatory effect of hymovis® on an in vitro model of CPP crystal-induced inflammation. Comparison with other hyaluronic acids used for intra-articular treatment. (23rd January 2014) - Oliviero, F.; Scanu, A.; Frallonardo, P.; Ramonda, R.; Sfriso, P.; Punzi, L.
Abstract : Background: Intra-articular injections of hyaluronic acid (HA) are widely used in the treatment of inflammatory and degenerative joint diseases. A novel slightly modified hyaluronic acid, HYADD4 (Hymovis®), has recently been tested in an ovine meniscectomy model of osteoarthritis, causing a reduction of vascularity and intimal hyperplasia, and an increase in the synthesis of high molecular weight HA by synovial fibroblasts (1). HYADD4 is a modified hyaluronate where the polysaccharidic backbone is derivatized with hexadecylic (C-16) side chains, through amide bonds, with a 1–3 mol % degree of substitution of repeating units. At a concentration as low as 0.3% (w/v) HYADD4 forms a gel, while unsubstituted hyaluronic acid forms viscous solutions at concentrations that are ten times higher. Objectives: The purpose of this study is to investigate the effect of HYMOVIS on an in vitro models which reproduces some inflammatory aspects of the osteoarthritis process. Methods: Synthetic calcium pyrophosphate (CPP) crystals (0.025mg/ml) were used to stimulate a monocytic cell line (THP-1), pre-activated with phorbol myristate acetate 50ng/ml, in presence or absence of Hymovis® (0.5 mg/ml). The production of IL-1β and IL-8 were determined in the supernatants along with the chemoattractant activity on polymorphonuclear cells. The results were compared with those obtained using 2 other types of HA (Hyalubrix® and Hyalgan®). The scavenger effect of Hymovis® on cytokines were investigated through the quantification of the trapping of these proteins to the chemical structure of HYADD4 and the others HA. The stimulation with LPS was used as control. Results: Hymovis® has shown a strong effect on the inhibition of the production of IL-1β (from 1750±230 pg/ml to 120±52 pg/ml). Although of smaller intensity, this effect was observed also using the other HA (Hymovis>Hyalubrix>Hyalgan). The anti-inflammatory property of Hymovis was also evident on the release of IL-8 (from 2300±315 pg/ml to 150±35 pg/ml) and on the migration of polymorphonuclear cells. The inhibitory effect of IL-8 release was confirmed after stimulation with LPS. All the 3 types of HA have shown to possess a little capacity to trap IL-1β (about 20%) while any scavenger effect was observed towards IL-8. Conclusions: The hexadecylic derivative of HA Hymovis® has shown a potent anti-inflammatory action on the released of pro-inflammatoy mediators upon stimulation with CPP crystals, frequently associated with more severe and advanced OA. Due to the physical-chemical property of HA preparations, it was likely that its coating on crystals might determine a lower inflammatory activity of crystals themselves. We were able to exclude this hypothesis testing a different stimuli as LPS. The little scavenger effect of all HA towards IL-1β does not account for the observed anti-inflammatory effect as well. It is possible that Hymovis® is able to protect cells from the extracellular compartments where inflammatory stimuli are present. The investigation of IL-1β and IL-8 at the transcriptional level will be evaluated to confirm this hypothesis. References: MM Smith, MA Cake, P Ghosh, A Schiavinato, R A Read, CB Little. Rheumatology 2008; 47: 1172. Disclosure of Interest: None Declared